Two Approvals from the 1931 Athens Conference: Anastylosis and International Collaboration for Architectural Conservation: New Evidence. (3rd April 2017) - Ohba, Go
Abstract: The Athens Conference was an international meeting on architectural conservation, organized by the International Museums Office, an institution that belonged to the League of Nations, in October 1931. The discovery of official documents, such as the minutes and statements of participants, clarifies discussions for all nine sessions. This study addresses approvals of the restoration measure, anastylosis, and the worldwide safeguard for historic monuments. Furthermore, it argues that the Athens Conference was the first global meeting in the twentieth century to frame modern conservation principals in terms of a role model for archaeological interventions and global aids for architectural protection.